Autoidentyfikacja i doświadczenie ciała w Autobiografii mistycznej Marianny Marchockiej - Bobrowska, Aleksandra (Poznańskie Studia Teologiczne, 2012)
Researchers agree that Mystical Autobiography of Marianna Marchocka, written at the end of the 1640’s and published in 1939 by Karol Górski, is an extraordinary phenomenon in 17th-century Polish literature, especially in Polish mystical literature. The Autobiography, compared with such works as the Autobiography of Teresa of Ávila, testifies to spiritual development of the Carmelite, provides a psychological study and a thorough record of female body experience. Despite the negativistic attitude of the nun to her body, as emphasized by researchers, both spirit and body were engaged in the mystical experiences of Marianna Marchocka – the body was involved in the experience of union with Jesus Christ. This article is an attempt to analyze spiritual and bodily signs of the Carmelite’s experience of a mystical relationship with God. Knowledge of the author’s personality and her attitude to her work, just like the analysis of mystical elation described in the Autobiography (paying special attention to the nun’s psyche and spirituality, and extraordinary bodily experience accompanying ecstasy) would not be possible without examining the genesis of the work, the importance that Marchocka attached to the act of writing itself and the author’s writing skills. What is of interest here is not only the bond between the Carmelite’s physicality and spirituality and her inner experiences and relationship with God, but also the literary expression of her attitude to her psyche and body.